Understanding the evolving threat landscape – APT techniques in a container environment. Issue 12 (December 2021) - Morag, Assaf; Maouda, Itamar
Abstract : State-sponsored threat actors are known to use the most advanced malware and advanced persistent threat (APT)-grade techniques to increase their impact and chances of success.